(untitled) (Plant Bulletin, 2025)
Cucurbit aphid-borne yellows virus (CABYV) poses a significant threat to cucurbit crops worldwide. This study provides insight into RNA-dependent RNA polymerase and coat protein regions of CABYV isolates infecting ridge gourd (Luffa acutangula) in Pakistan. Field surveys in the Lahore district revealed that ridge gourd plants have severe interveinal yellowing and vein thickening symptoms (usually associated with polerovirus infection) and a 10–40% disease incidence. PCR amplification by polerovirus group-specific primers and sequencing confirmed CABYV infection in 9 of 20 samples. In phylogenetic reconstruction, the Pakistani isolates clustered with isolates from Taiwan and Indonesia, and the BLAST analysis showed >90% sequence similarity with these isolates highlighting CABYV’s global genetic diversity. These findings underscore the need for comprehensive surveys and genomic studies to develop sustainable management strategies for this destructive pathogen.